Smartphone interactions and mental well-being in young adults: A longitudinal study based on objective high-resolution smartphone data. Issue 3 (May 2021) - Dissing, Agnete Skovlund; Hulvej Rod, Naja; Gerds, Thomas A.; Lund, Rikke
Aims: To investigate the effects of objectively measured smartphone interactions on indicators of mental well-being among men and women in a population of young adults. Methods: A total of 816 young adults (mean±SD age 21.6±2.6 years; 77% men) from the Copenhagen Network Study were followed with objective recordings of smartphone interactions from calls, texts and social media. Participants self-reported on loneliness, depressive symptoms and disturbed sleep at baseline and in a four-month (interquartile range 75–163 days) follow-up survey. Multiple linear regression was used to analyse the association between smartphone interactions and mental well-being separately for men and women. Results: A higher number of smartphone interactions was associated with lower levels of loneliness at baseline and the same pattern appeared for depressive symptoms, although this was less pronounced. A high level of smartphone interaction was associated with lower levels of disturbed sleep for men, but not for women. In follow-up analyses, a high versus low level of smartphone interaction was associated with an increase in loneliness and depressive symptoms over time for women, but not for men. Conclusions: Smartphone interactions are related to better mental well-being, which may be attributed to the beneficial effects of an underlying social network. Over time, accommodating a large network via smartphone communication might, however, have negative effects on mental well-being for women.